Oriental Sources in West African Oral Literature: A Medieval Arabic Romance in Bamana Translation - (:unkn) unknown (My University, 2013)
Analysis of West African oral lore, including epics, historical legends, folktales, and genealogies, shows that many personages, narrative sequences, and even stylistic devices are drawn from Arabic literature. The most influential Arabic works include: the Koran; ḥadīth collections and other works pertaining to the words and deeds of the Prophet Muhammad; the qiṣaṣ al-anbiyāʾ – tales pertaining to the pre-Islamic (Israelite and early Arabian) prophets; tales from the Kalīla wa-Dimna, the Alexander cycle, and the Thousand and One Nights; the « folk romances » or « folk epics » (sīra); and pre-Islamic poetry. It is hypothesised that most of these texts, many of which themselves draw on older literatures (Ancient Egyptian, Mesopotamian, Persian, Indian...), entered West Africa in written form, then were orally translated into and transmitted in the local languages. The study concludes with a passage (in Bamana transcription and French translation) from the romance of Sayf b. Dhī Yazan as it was orally translated by a scholar from Segu, Mali, for a circle of his friends.
Keywords: African Research